Determinan Tax Avoidance Berdasarkan Profitabilitas, Leverage dan Komite Audit dan Dampaknya terhadap Nilai Perusahaan - Emma - Lilianti; Jusmani Jusmani Jusmani; Andri Eko Putra (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2021)
This study aims to determine the amount of tax avoidance which is directly influenced by profitability, leverage, the audit committee, as well as to determine the indirect effect of profitability, leverage, and the audit committee on firm value through the tax avoidance variable. population of 23 issuers of the coal sub-sector using purposive sampling obtained a sample of 19 issuers from the 2016-2019 observation year.This research method uses a quantitative approach and focuses on empirical testing between independent and dependent variables. The analysis model uses path analysis. Path analysis is translated by 2 regression equations to test the effect of the independent variable on the moderating variable and the effect of the independent variable on the independent variable through the moderating variable. The results of testing the t hypothesis show a direct and significant effect of profitability and leverage on tax avoidance, while the audit committee has no significant effect on tax avoidance. Tax avoidance directly has a significant and negative effect on firm value. For the indirect effect, profitability and leverage have a significant effect on firm value, while the auditcommittee has no effect on firm value in the coal sub-sector on the IDX.